The noble identity of Gavin Douglas - Royan, Nicola (Oxford University Press, 2017)
This essay takes up Sally Mapstone’s contention that Scottish advice to princes was directed as much to magnates and their supporters as it ever was to the king, and applies it to Gavin Douglas’s Eneados. It considers the manner in which Douglas’s translation represents nobility, national identity, and political violence, with reference to Douglas’s own magnatial identity and that of the poem’s patron, William Sinclair. It considers both the prologues and the translated texts, examining further the relationship between them. In so doing, it places the Eneados in the context of Virgilian criticism as well as Older Scots poetic traditions, and demonstrates parallels in language choices regarding war, government, and rule.